Nazi victims on the dissection table — The Anatomical Institute in Innsbruck - Czech, Herwig; Brenner, Erich (Annals of anatomy, 2019)
Since Vienna University’s 1997/98 inquiry into the background of Eduard Pernkopf’s anatomical atlas, German and Austrian anatomical institutes have been forced to confront their past, particularly the widespread procurement of bodies of victims of National Socialism. This paper focuses on the Anatomical Institute in Innsbruck, which received bodies from an unusually broad array of sources: from prisoners executed at Stadelheim Prison in Munich, prisoners of war from three different camps, military personnel sentenced to death by martial courts, patients from a psychiatric hospital, and several bodies of Jewish Holocaust victims. As in other comparable cases, these bodies were used for scientific publications and medical teaching until long after the war. The Anatomical Institute’s collection is currently undergoing a detailed analysis in order to identify any human remains dating from the Nazi period. At the Institute of Histology and Embryology, recent research has led to the discovery of approximately 200 histological slides pertaining to at least five individuals who had been executed under the Nazi regime. In a number of cases, the specimens had been provided by Prof. Max Clara, head of the Leipzig Institute of Anatomy. This study is based on an analysis of the Innsbruck Anatomical Institute’s unusually detailed records and numerous documents from various archives, including files pertaining to an inquiry into the institute held after the war by the French occupation authorities.